PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN: (Studi Kasus PT.SINAR SOSRO Rancaekek) - Kirana Vallennia; Atik Atikah; Fitri Nur Azijah (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2020)
Employee performance has a major contribution in achieving the company's goals of PT. Sinar Sosro by prioritizing product quality for the community. This research aims to analyze the effect of work discipline on employee performance. The research location is conducted at PT. Sinar Sosro which is located on Jl. Raya Rancaekek km 26, 5 Bandung. The study used a sample of 30 people with primary and secondary data sources and data analysis techniques of regression equations, and the coefficient of determination. The results of this study prove that the resulting regression equation shows that work discipline has a positive and significant effect on the performance of employees of PT. Sinar Sosro Rancaekek . The coefficient of determination shows the magnitude of the effect of work discipline on the performance of employees of PT. Sinar Sosro Rancaekek 21.9% while the rest is influenced by other factors besides work discipline. The calculation results show a fairly small percentage of work discipline on employee performance is only 24.9%, so other factors are believed to have a big influence in influencing employee performance and need to be reexamined. This study concludes that work discipline has a significant influence on the performance of PT.Sinar Sosro Rancaekek.